2016
DOI: 10.1111/nph.13853
|View full text |Cite
|
Sign up to set email alerts
|

Leaf aging of Amazonian canopy trees as revealed by spectral and physiochemical measurements

Abstract: SummaryLeaf aging is a fundamental driver of changes in leaf traits, thereby regulating ecosystem processes and remotely sensed canopy dynamics.We explore leaf reflectance as a tool to monitor leaf age and develop a spectra-based partial least squares regression (PLSR) model to predict age using data from a phenological study of 1099 leaves from 12 lowland Amazonian canopy trees in southern Peru.Results demonstrated monotonic decreases in leaf water (LWC) and phosphorus (P mass ) contents and an increase in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 88 publications
14
141
0
1
Order By: Relevance
“…Some of most accurately predicted traits have no absorption features in the visible-to-near-infrared, but were instead estimated indirectly via constellation effects. LMA is consistently among the more accurately predicted traits using spectroscopy (Asner and Martin, 2008;Serbin et al, 2014;Chavana-Bryant et al, 2016), but is measured indirectly via its close coupling with water content and structural traits of leaves (Asner et al, 2011b). Silicon (Si) concentrations were well predicted by field spectroscopy, as recently reported by Smis et al (2014).…”
Section: Measuring Interspecific Variation In Leaf Traitsmentioning
confidence: 58%
“…Some of most accurately predicted traits have no absorption features in the visible-to-near-infrared, but were instead estimated indirectly via constellation effects. LMA is consistently among the more accurately predicted traits using spectroscopy (Asner and Martin, 2008;Serbin et al, 2014;Chavana-Bryant et al, 2016), but is measured indirectly via its close coupling with water content and structural traits of leaves (Asner et al, 2011b). Silicon (Si) concentrations were well predicted by field spectroscopy, as recently reported by Smis et al (2014).…”
Section: Measuring Interspecific Variation In Leaf Traitsmentioning
confidence: 58%
“…Some studies [62] have found a dramatic increase in leaf NIR reflectance between July and August, which might be caused by differences in the leaf characteristics. Low-wax leaves display a continuous increase in NIR reflectance until maturity, while high-wax leaves show little increase in NIR reflectance [63]. Epicuticular waxes and thick cuticles could mask the effect of NIR increases caused by inter-cellular development in young high-wax leaves.…”
Section: Spectral Changes and Leaf Agingmentioning
confidence: 99%
“…In order to promote spectral based monitoring of similar kinds of vegetation systems, it may be useful to collect data throughout different phenological stages and identify time periods when the discrimination between key species is clearest. Characterizing the spectral changes through time would also be useful to interpret associated changes in vegetation biophysical/chemical properties; for example Chavana-Bryant et al [80] proposed a statistical model to monitor leaf age and related traits by tracing changes in their reflectance.…”
Section: Functional Traits As Ecosystem Monitoring Toolmentioning
confidence: 99%